chetan2u wrote:
If a, b, and c are positive integers, a - b = ?
(1)\( 3^a 7^b = 21^c..........3^a7^b=3^c7^c\)
Equating powers, we get a=c and b=c. OR a=b=c
Thus a-b=0
Sufficient
(2)\( a = c = 10\)
Nothing about b
A
Could you possibly throw some light on this question?
Like, if I didn't know that a, b and c are positive integers I wouldn't have been able to solve this one right?
Or, Rather than saying
find (a - b) if we were asked to find the value of a then it would have been insufficient right?
The way I see this sum is that there isn't any Exponential property being used. Just some baisc logical understanding.
Posted from my mobile device